Perceptions and use of recovery strategies: Do swimmers and coaches believe they are effective? - Shell, S. J.; Slattery, K.; Clark, B.; Broatch, J. R.; Halson, S.; Kellmann, M.; Coutts, A. J. (Journal of Sports Sciences, 2020)
This study aimed to investigate swimmer`s use and coach prescription of recovery strategies during training and competition while examining perceived challenges, barriers, and beliefs in the importance of their effectiveness. A mixed-methods sequential explanatory design was implemented. Thirty-seven male and 45 female sub-elite to elite swimmers (age 18 ± 3 y), and 4 male and 6 female coaches (age 40 ± 9 y) completed an online, 78-item recovery strategy survey. Swimmers and coaches responded to questions regarding when, why, and how they used recovery strategies, perceived challenges and barriers to strategy inclusion during training and competition. Data were coded and analysed thematically. Fisher`s Exact Test was conducted on 5-point Likert scale responses. Most recovery strategies were used and prescribed more during competition. Swimmers reported active recovery as the most effective recovery strategy (44%), whereas coaches rated sleep or napping (40%). Swimmers and coaches perceived most recovery strategies to be more effective and important during competition than in training. Swimmers used, and coaches prescribed, recovery strategies more during the competition, highlighting the discrepancies in use between training and competition. Targeted education programmes should enhance athletes and coach`s recovery knowledge and practical application of strategies, while accounting for individual sport and life demands.